(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Despite the adoption of landmark legal acts for the formation of the waste management system, there is no guarantee that changes will occur. After all, environmental consciousness and responsibility have not been formed at the level of the average Ukrainian. There is no clear understanding at the regional and local levels of what to do with waste and what profit can be made if it is recycled. Program measures are implemented in an incomplete volume due to a shortage of financial and investment resources. The purpose of the article. The purpose of the article is to determine the factors influencing the formation of an effective regional household waste management system in Ukraine. To achieve the goal, the following tasks were solved: to consider the concepts of «waste management system», «household waste management», «regional household waste management system», to determine the factors influencing the generation and disposal of household waste in order to provide conditions for the formation of effective regional its management systems. Results. The interpretation of the concept of «regional household waste management system» is presented. The features that determine the functioning of household waste management systems at the regional level are determined. A number of problems inherent in the field of local waste management are highlighted. The main features of the functioning of the domestic household waste management system are indicated. The basic unit in the waste management system is argued. The hierarchical structure of the regional waste management system is presented. The organizational and economic factors that determine the volume and structure of waste generation/disposal and to which we primarily refer the macroeconomic situation in the country, the economic activity of enterprises, waste logistics, economic and environmental levers and production limitations are substantiated. A group of innovative and technological factors influencing the formation of waste management systems is singled out, in particular the technical and technological level of production and utilization capacities, investment activity and access to credit resources. The effect-forming role of the socio-legal group of factors is emphasized, which include the level of environmental awareness of waste generators, responsibility for violation of technological standards, the ability to organize the sorting of household waste, state priorities for the implementation of waste management policy, legal responsibility for unauthorized handling with waste. Conclusions. The formation of a waste management system according to European standards requires significant financial and investment resources. This will make it possible to expand opportunities in the provision of quality services in the field of waste management, and by increasing the quality level of disposal activities, the regions of Ukraine will be able to ensure quality standards of the ecological state of the territory and their sustainable development.